2007
DOI: 10.1021/jo0705162
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Catalyzed Aza-Diels−Alder Reactions for the Total Synthesis of (±)-Lapatin B

Abstract: A 5-step total synthesis of microfungal alkaloid (+/-)-lapatin B has been accomplished via a key 2-aza-Diels-Alder reaction. Brønsted acids catalyze the cycloaddition step and provide improved exo selectivity. This synthetic route has been applied to the construction of related spiro-quinazoline structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The exo adduct 290b was transformed to 284 (Scheme 51). 105 A total synthesis of unnatural (À)-serantrypinone (292) from L-tryptophan has been reported. The key step involved the transformation of selenoxide 293 to acetate 294 via trapping of a presumed intermediate in a seleno-Pummerer reaction.…”
Section: Non-isoprenoid Tryptaminesmentioning
confidence: 99%
“…The exo adduct 290b was transformed to 284 (Scheme 51). 105 A total synthesis of unnatural (À)-serantrypinone (292) from L-tryptophan has been reported. The key step involved the transformation of selenoxide 293 to acetate 294 via trapping of a presumed intermediate in a seleno-Pummerer reaction.…”
Section: Non-isoprenoid Tryptaminesmentioning
confidence: 99%
“…In an earlier communication, 5 we reported the synthesis of (±)-lapatin B by implementing Kende's elegant approach to the synthesis of (±)-alantrypinone. 3 Lapatin B and alantrypinone arise from an exo orientation of dienophile 6 in the Diels-Alder cycloaddition with dienes 4 and 5, respectively (Scheme 1).…”
Section: Figure 1 Spiropolycyclic Alkaloidsmentioning
confidence: 99%
“…37,38 The first synthesis, from the Syntenta group in Switzerland, followed the Kende approach to alantrypinone and gave racemic material. The second synthesis followed the aforementioned routes to ent-alantrypinone and ent-serantrypinone and confirmed that the absolute configuration of lapatin B 9 is pseudoenantiomeric with alantrypinone 7 and serantrypinone 8.…”
Section: Total Synthesis Of Lapatin B (9)mentioning
confidence: 99%